MODERN APPROACHES TO ANTIVIRULENT THERAPY OF DISEASES ASSOCIATED WITH STAPHYLOCOCCUS AUREUS - T.O. Kryuchko; O.Ya. Tkachenko; N.V. Kuzmenko; I.N. Nesina; S.M. Tanianska; I.A. Kolenko; M.O. Melnyk (Проблеми екології та медицини, 2019)
Staphylococcus aureus is a universal bacterial pathogen, which is able to develop the resistance to new antibiotics, by means of virulence factors, whose main function is the spread of diseases by inhibiting the immune factors of host defense. Its wide spread at in-patient departments and also the presence of clinical probationary wards Staphylococcus aureus, resistant to methicillin at out-patient departments, deprive the doctors of effective means for control of the infection. Complications caused by MRSA lead to hospitalization and indices of lethality. The aim of the paper is to analyze the main factors of S. аureus virulence and ways the of its interaction as a result of etiological and pathogenetic treatment. Complexity of treatment of bacterial infections is determined by alternative ways of prevention and treatment of diseases to which bacteria are not able to develop resistance. Along with general mechanisms that form antibiotic resistance, S. aureus produces many individual virulence factors that model the immune response, affecting the survival of the microorganism. The virulence factors produced by S. aureus are diverse and have the ability not only to cause cell lysis, but also to stimulate tissue rejection and destruction. It is important to determine that many specific factors of virulence caused by S. aureus, have ability to change both congenital and adaptive immune reactions including inhibition of complement activation, neutrophils neutralization, phagocytes inhibition. Strategies for inhibiting virulence factors can range from using small inhibitor molecules or full-fledged antibodies to creating toxoids and virulence proteins. Great interest is focused upon those inhibitors that have cross-reactivity with respect to multiple virulence factors, as well as inhibitors, the main target of which is a global regulator with multi-purpose activity, for example, agr operon. Active research into the specific alternative antivirulent treatments for severe diseases caused by S. aureus can potentially settle a number of problems and difficulties of post-antibiotic era.